1997
DOI: 10.1002/(sici)1097-0215(19970410)71:2<159::aid-ijc6>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

International incidence rates of invasive cervical cancer before cytological screening

Abstract: Huge differences in incidence rates of invasive cervical cancer occur among populations. These differences reflect the influences of both etiological environmental factors and removal of precursor lesions detected upon screening. The purposes of this article are (i) to describe similarities and differences in the shapes and magnitudes of age-specific incidence rates of invasive cervical cancer before screening had an effect, (ii) to provide baseline data for further global study of screening effects, and (iii)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
250
0
16

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(274 citation statements)
references
References 12 publications
8
250
0
16
Order By: Relevance
“…This prediction is consistent with the literature where peaks are reported between 44 and 49 years for European countries 52 and lifetime risks between 2.5% and 3.7%. 12,14,15,25,41 The predicted percentage of clinical cases in FIGO stage 1 is 40% and is consistent with a reported figure of 43%.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This prediction is consistent with the literature where peaks are reported between 44 and 49 years for European countries 52 and lifetime risks between 2.5% and 3.7%. 12,14,15,25,41 The predicted percentage of clinical cases in FIGO stage 1 is 40% and is consistent with a reported figure of 43%.…”
Section: Discussionsupporting
confidence: 93%
“…Epidemiologic studies report that in countries where cytologic screening has been implemented, the incidence of cervical cancer has shown a larger decrease than in countries without screening. 1,2 Although many countries subscribe to the necessity of screening, each country has its own screening program and different opinions about the optimal program remain.…”
mentioning
confidence: 99%
“…Other studies have also shown that within Europe, The Netherlands have a very low incidence, and a very high survival compared with other countries (Levi et al, 2000). It is reasonable to attribute these findings to the presence of a nationwide screening programme, as similar effects on incidence have been described in other countries with a screening programme (Gustafsson et al, 1997). Whether the effect on survival in the absence of changes in treatment can be exclusively attributed to the cervical cancer screening programme, remains a question of debate (Quinn et al, 1999;Sasieni and Adams, 1999).…”
Section: Incidence and Survival Of Cervical Cancer S Bulk Et Almentioning
confidence: 63%
“…Population-based cervical cancer screening has led to a decrease in the incidence of cervical cancer (Gustafsson et al, 1997;Vizcaino et al, 2000). However, recent data suggest that the decrease in incidence is caused by a decrease of squamous cell carcinoma, while the incidence of adenocarcinoma of the cervix shows no change or sometimes even an increase (Anttila et al, 1999;Bergstrom et al, 1999;Hemminki et al, 2001;Liu et al, 2001).…”
mentioning
confidence: 99%
“…Women with precancerous or cancerous lesions identified through Pap screening are referred for repeat Pap screening, colposcopy, biopsy and, where appropriate, treatment. The development and implementation of population-based Pap smear screening programmes for the early detection of pre-cancerous cervical lesions, together with aggressive treatment of women with abnormal biopsies, are thought to be largely responsible for the significantly reduced incidence of and mortality from ICC seen in many developed countries since the 1950s [8,[35][36][37][38][39].…”
Section: Prevention Of Cervical Cancer Secondary Prevention : Cytologmentioning
confidence: 99%